Circannual variability of calcium and phosphorus serum levels in foal and calf: a comparison. Issue 3 (16th March 2021) - Saoca, Concetta; Rizzo, Maria; Giannetto, Claudia; Fazio, Francesco; Giudice, Elisabetta; Panzera, Michele; Piccione, Giuseppe
ABSTRACT: The annual trend of serum calcium and phosphorus serum levels in growing foals and calves was studied, in order to evaluate the possible circannual rhythmicity of these hematochemical parameters. For this purpose, eight Standardbred foals and eight Charolais calves, all 120 days old and coming from two Sicilian farms, were monitored for a period of 12 months, from June (T1) to May (T12) of the following year. Blood samples were collected from each animal every 30 days (at 12 time points) throughout the experimental period, in order to assess the monthly values of serum calcium and phosphorus. The analysis of variance showed a significant effect of time for the studied parameters in both species. Significant differences were observed between foals and calves for calcium at T4 and T9, and for phosphorus at T6, T7, T9 and T10. The cosinor-rhythmometry showed an annual rhythm of serum calcium and phosphorus levels, both in foals and calves. Our research wants to represent a contribution to the study of identification of those external and internal synchronizers necessary to establish the specific temporal organization of a biological process, and contributes to the knowledge on the temporal trend of these blood parameters in foal and calf.